Bub1p Kinase Activates the Saccharomyces cerevisiae Spindle Assembly Checkpoint - Farr, Katie A. (American Society for Microbiology, 1998)
Saccharomyces cerevisiae BUB1 encodes a protein kinase required for spindle assembly checkpoint function. In the presence of spindle damage, BUB1 is required to prevent cell cycle progression into anaphase. We have identified a dominantly acting BUB1 allele that appears to activate the spindle assembly checkpoint pathway in cells with undamaged spindles. High-level expression of BUB1-5 did not cause detectable spindle damage, yet it delayed yeast cells in mitosis at a stage following bipolar spindle assembly but prior to anaphase spindle elongation. Delayed cells possessed a G(2) DNA content and elevated Clb2p mitotic cyclin levels. Unlike cells delayed in mitosis by spindle damage or MPS1 kinase overexpression, hyperphosphorylated forms of the Mad1p checkpoint protein did not accumulate. Similar to cells overexpressing MPS1, the BUB1-5 delay was dependent upon the functions of the other checkpoint genes, including BUB2 and BUB3 and MAD1, MAD2, and MAD3. We found that the mitotic delay caused by BUB1-5 or MPS1 overexpression was interdependent upon the function of the other. This suggests that the Bub1p and Mps1p kinases act together at an early step in generating the spindle damage signal.